2017
DOI: 10.1080/10790268.2017.1301622
|View full text |Cite
|
Sign up to set email alerts
|

Quality reporting of carotid intima-media thickness methodology; Current state of the science in the field of spinal cord injury

Abstract: A greater adherence to current methodological guidelines is needed to advance the field of cIMT in SCI. Further research is necessary to refine cIMT acquisition and analysis guidelines to aid authors designing research and journals in screening manuscripts for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…22 IMT has previously been measured in younger people with SCI (mean ages 22-43 years) and mostly in men, which limits comparisons. 23 The study by Wang et al 7 and another study by Bell et al 24 (105 participants with SCI, mean age 41 years, and 156 controls) showed comparable IMT in the CCA of participants and controls (0.60 vs. 0.60, and 0.61 vs. 0.59, respectively). These two studies are in agreement with our findings of IMT in the CCA (0.68 among the participants vs. 0.70 among the controls).…”
Section: Participants With Scimentioning
confidence: 90%
See 1 more Smart Citation
“…22 IMT has previously been measured in younger people with SCI (mean ages 22-43 years) and mostly in men, which limits comparisons. 23 The study by Wang et al 7 and another study by Bell et al 24 (105 participants with SCI, mean age 41 years, and 156 controls) showed comparable IMT in the CCA of participants and controls (0.60 vs. 0.60, and 0.61 vs. 0.59, respectively). These two studies are in agreement with our findings of IMT in the CCA (0.68 among the participants vs. 0.70 among the controls).…”
Section: Participants With Scimentioning
confidence: 90%
“…Increased IMT is not atherosclerosis per se but a surrogate marker predicting CVD 22 . IMT has previously been measured in younger people with SCI (mean ages 22–43 years) and mostly in men, which limits comparisons 23 . The study by Wang et al 7 and another study by Bell et al 24 (105 participants with SCI, mean age 41 years, and 156 controls) showed comparable IMT in the CCA of participants and controls (0.60 vs. 0.60, and 0.61 vs. 0.59, respectively).…”
Section: Discussionmentioning
confidence: 99%